The Behavior of Nontradable Goods Prices in Europe : Evidence and Interpretation - De Gregorio, Jose (IMF Working Papers; Working Paper ;, 1993)
This paper examines the evolution of the relative price between tradable and nontradable goods in a group of European countries. A model of an open economy is used to analyze different factors that can account for an increase in the relative price of nontradable goods. These factors are: (a) faster technological progress in the tradable goods sector; (b) demand shifts toward nontradable goods; and (c) real wage pressures. The relevance of these factors is analyzed empirically for France, Germany, Italy, Spain and the United Kingdom.